Actual and Potential Trade Agreements in the Asia-Pacific : Estimated Effects - Ferrantino, Michael J. (World Bank, Washington, DC, 2020)
This paper assesses and compares economic impacts of four actual and potential free trade agreements in the Asia-Pacific Region; Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP, sometimes also called TPP-11), the original Trans Pacific Partnership (TPP-12), the Regional Comprehensive Economic Partnership (RCEP), and the Free Trade Area of the Asia-Pacific (FTAAP). FTAs with a larger scale and wider membership are expected to produce higher aggregate gains in terms of increased GDP and trade flows. U.S. withdrawal from TPP-12 reduced estimated GDP gains for the TPP-11 countries by about half. For countries belonging to CPTPP and also negotiating RCEP, the potential gains from an agreement with both China and Korea are substantial, but not as large as if the United States were to re-join TPP-12. On a sectoral basis, significant structural shifts are observed for such sectors as food processing, wearing apparel, textiles, and transport equipment.